2002
DOI: 10.1002/1439-7633(20020301)3:2/3<246::aid-cbic246>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Binding Modes Observed in Trypsin Crystals: Lessons for Structure‐Based Drug Design

Abstract: Drug lead compound identification increasingly uses high‐throughput screening in conjunction with computational methods. Hits found in this way are generally of low affinity (typically about 10−5 M) and require further development. Such low affinity can result in significant changes in binding mode upon change of experimental conditions: at pH 7, the Factor Xa inhibitor 1 (see picture) binds in the specificity pocket of trypsin through its pyridinyl group (yellow); at pH 8, the same pocket is occupied by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 17 publications
4
42
0
3
Order By: Relevance
“…91 A variety of data suggests this same conclusion may hold true in a variety of other systems. 20,68,88,[97][98][99][100][101][102][103] Going beyond ligand orientation, closely related ligands can bind with significantly different protein conformations. Protein conformational changes can be important, and even protein side chain differences in the binding site can be slow and, calculations indicate, thermodynamically significant.…”
Section: E Binding Modes Are Difficult To Predictmentioning
confidence: 99%
“…91 A variety of data suggests this same conclusion may hold true in a variety of other systems. 20,68,88,[97][98][99][100][101][102][103] Going beyond ligand orientation, closely related ligands can bind with significantly different protein conformations. Protein conformational changes can be important, and even protein side chain differences in the binding site can be slow and, calculations indicate, thermodynamically significant.…”
Section: E Binding Modes Are Difficult To Predictmentioning
confidence: 99%
“…This has been recently revealed in a study of trypsin crystals [50], which shows the occurrence of protonation and crystal form dependent binding modes. For a series of aliphatic cyclic ureas bound to HIV-1 protease, the binding energies computed by the Poisson equation significantly depend on the protonation state of the two active site aspartic acids [51].…”
Section: Electrostatics Of the Interactionsmentioning
confidence: 99%
“…This "chlorobinding" motif, first reported in 1998 by Tucker et al [97] for thrombin-inhibitors with neutral S1 groups, was then identified by several groups as an important contributor to binding affinity in serine proteases, respectively [98][99][100][101][102]. This interaction of chlorine with the aromatic ring system of Tyr228 is shown in Figure 8.5a (PDB 1TA6, resolution 2.3Å).…”
Section: Literature Investigations On Halogen Aromatic Interactmentioning
confidence: 99%